PERSEPSI ANAK PEREMPUAN TERHADAP POLA ASUH AYAH TUNGGAL - Latifah Hidayati; Andhita Dyorita Khoiryasdien (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
Single-father parenting presents challenges in meeting a daughter’s developmental and emotional needs, particularly within a patriarchal cultural context. This study aimed to describe a daughter’s perception of single-father parenting and the psychological experiences associated with it. The study employed a qualitative approach with a case study design. The participant was a 19-year-old woman living in Bantul, Yogyakarta, who had been raised by her single father since the age of 10 following her mother’s death. Data were collected through in-depth interviews, transcribed verbatim, coded, and analyzed thematically. Four main themes emerged. First, paternal control gradually shifted toward trust as the participant grew older, although the father tended to remain silent when disappointed. Second, discipline and logical consequences were perceived as contributing to the participant’s independence and sense of responsibility, while expectations to contribute financially created pressure. Third, communication primarily focused on practical matters, whereas emotional concerns were rarely discussed because the participant felt that her experiences were not always validated. Fourth, paternal affection was expressed more frequently through concrete actions, companionship, and shared time than through verbal expressions or physical affection. These findings indicate that, in the participant’s experience, single-father parenting supported independence and responsibility but remained limited in terms of emotional openness and closeness. ABSTRAK Pengasuhan oleh ayah tunggal menghadirkan tantangan dalam memenuhi kebutuhan perkembangan dan emosional anak perempuan, terutama dalam konteks budaya patriarki. Penelitian ini bertujuan menggambarkan persepsi seorang anak perempuan terhadap pengasuhan ayah tunggal serta pengalaman psikologis yang menyertainya. Penelitian menggunakan pendekatan kualitatif dengan desain studi kasus. Partisipan adalah seorang perempuan berusia 19 tahun di Bantul, Yogyakarta, yang diasuh oleh ayah tunggal sejak usia 10 tahun setelah ibunya meninggal dunia. Data dikumpulkan melalui wawancara mendalam, ditranskripsikan secara verbatim, dikodekan, dan dianalisis secara tematik. Hasil penelitian menunjukkan empat tema utama. Pertama, kontrol ayah berkurang dan berkembang menjadi kepercayaan seiring bertambahnya usia partisipan, meskipun ayah cenderung memilih diam ketika kecewa. Kedua, kedisiplinan dan konsekuensi logis dipersepsikan berkontribusi terhadap perkembangan kemandirian dan tanggung jawab, tetapi harapan untuk berkontribusi secara finansial menimbulkan tekanan bagi partisipan. Ketiga, komunikasi lebih banyak berfokus pada persoalan praktis, sedangkan masalah emosional jarang dibicarakan karena partisipan merasa tidak selalu memperoleh validasi. Keempat, kasih sayang ayah lebih sering diwujudkan melalui tindakan nyata, pendampingan, dan waktu bersama daripada melalui ungkapan verbal atau afeksi fisik. Temuan ini menunjukkan bahwa pengasuhan ayah tunggal dalam pengalaman partisipan mendukung kemandirian, tetapi masih memiliki keterbatasan dalam keterbukaan dan kedekatan emosional.